Nitrogen and potassium fertigation in bell pepper cultivated in greenhouse using fertigation managements - Nunes Junior, Edivan S.; Medeiros, Jose F. de; Oliveira, Francisco de A. de; Lima, Luan A.; Bezerra, Francisco M. S.; Alves, Rita de C. [UNESP] (Univ Federal Campina Grande, 2017)
The objective of the study was to evaluate the effect of different managements of fertigation and NK doses on the production of bell pepper fruit in a protected environment. The experimental design was randomized blocks in 3 x 5 factorial. The treatments were formed by the combination of three managements of fertigation (M-1 - Based on the rate of absorption; M-2 - Monitoring the electrical conductivity of the soil solution; M-3 - Monitoring concentrations of N and K ions in the soil solution), with five doses of NK (0, 50, 100, 150 and 200% of the recommended dose) and four replicates. Six samples were collected and the following variables were evaluated: number, length and diameter of fruit, pulp thickness and fruit production. Except for diameter, all variables were affected by the interaction between the studied factors. The fertigation management by monitoring and controlling the ionic concentration of the soil solution is more efficient in the production of bell pepper. The fertigation management can be performed more efficiently from the managements M2 or M3, with NK doses of 144 and 165%, respectively, of the recommended concentration for the hydroponic cultivation of bell pepper.
Keywords: Capsicum annuum L.; soil solution; salinity; ionic concentration